2001
DOI: 10.1054/bjoc.2001.1869
|View full text |Cite
|
Sign up to set email alerts
|

CGH analysis of ductal carcinoma of the breast with basaloid/myoepithelial cell differentiation

Abstract: 2–18% of ductal carcinoma-No Special Type (NST) are reported to express basal cell keratin 14 and such tumours may have a different metastatic pattern and prognosis. We performed immunohistochemistry for cytokeratins 19 (luminal) and 14 (basal) on 92 ductal carcinoma-NST. Those tumours showing CK14 expression were further characterized by immunohistochemistry for myoepithelial cell phenotype and analysed by comparative genomic hybridization. The 7 cases of ductal carcinoma-NST exhibiting a basal cell phenotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
108
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(120 citation statements)
references
References 32 publications
12
108
0
Order By: Relevance
“…This may explain the small number of cases showing positive immunoreactivity for the basal cytokeratins CK14 and CK5/6 in our study. 5 It has been reported that between 2-18% of infiltrative ductal cancers show expression for CK14, 18 and our finding of CK14 positivity in 11.2% of breast cancers from our young women lies within this range. Fewer cases were reactive for CK5/6 as compared with CK14, which could be related to differences in sensitivity of the antibodies, as noted in our study on papillary breast lesions.…”
Section: Discussionsupporting
confidence: 75%
“…This may explain the small number of cases showing positive immunoreactivity for the basal cytokeratins CK14 and CK5/6 in our study. 5 It has been reported that between 2-18% of infiltrative ductal cancers show expression for CK14, 18 and our finding of CK14 positivity in 11.2% of breast cancers from our young women lies within this range. Fewer cases were reactive for CK5/6 as compared with CK14, which could be related to differences in sensitivity of the antibodies, as noted in our study on papillary breast lesions.…”
Section: Discussionsupporting
confidence: 75%
“…In conclusion, the study has demonstrated the biological, pathological and clinical features of FABP7 and OATP2 protein expression in human breast carcinoma and with respect to FABP7 particularly its relationship and significance in BP breast cancer [12,13,15,18,22,23,25,28,43,54]. These novel biomarkers have significant associations, both independently and within the BP, on tumour behaviour, expression of other biomarkers, and clinical outcome.…”
Section: Discussionmentioning
confidence: 78%
“…The basal-like type or BP of breast cancer has been subject to extensive investigation in recent years, mainly due to its association with poor patient survival [13,15,22,23,43,44]. Despite this interest, there is currently no robust definition for designation of "basal-like" or BP breast cancer in routine clinical practice, furthermore tumours with a BP are also now recognised to exhibit heterogeneity [14,23].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations